2014
DOI: 10.1007/s00425-014-2182-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutrient remobilization through structural changes of palisade and spongy parenchyma in oilseed rape leaves during senescence

Abstract: Differential palisade and spongy parenchyma structural changes in oilseed rape leaf were demonstrated. These dismantling processes were linked to early senescence events and associated to remobilization processes. During leaf senescence, an ordered cell dismantling process allows efficient nutrient remobilization. However, in Brassica napus plants, an important amount of nitrogen (N) in fallen leaves is associated with low N remobilization efficiency (NRE). The leaf is a complex organ mainly constituted of pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
49
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 37 publications
13
49
4
Order By: Relevance
“…Thus, the variation of the T 2 in LR 8 and LR 4 at 57 DAS is logical. However, the older leaves studied (LR4) of stressed plants had begun senescence at 57 DAS as shown by the increase in T 2-3 and LWW 3 whereas T 2-2 remained stable, which is typical of the progression of senescence previously reported in oilseed rape leaves [35]. For these leaves, most of the vacuolar water was associated with the spongy cells vacuoles at 42 DAS, but this fraction decreased after 57 DAS to the benefit of the water fraction associated with the vacuoles of the palisade cells.…”
Section: Leaves At Two Developmental Stages Monitored Through Nmrsupporting
confidence: 61%
See 3 more Smart Citations
“…Thus, the variation of the T 2 in LR 8 and LR 4 at 57 DAS is logical. However, the older leaves studied (LR4) of stressed plants had begun senescence at 57 DAS as shown by the increase in T 2-3 and LWW 3 whereas T 2-2 remained stable, which is typical of the progression of senescence previously reported in oilseed rape leaves [35]. For these leaves, most of the vacuolar water was associated with the spongy cells vacuoles at 42 DAS, but this fraction decreased after 57 DAS to the benefit of the water fraction associated with the vacuoles of the palisade cells.…”
Section: Leaves At Two Developmental Stages Monitored Through Nmrsupporting
confidence: 61%
“…This study proved the ability of low field NMR to monitor these developmental processes in tobacco leaves. Our team [35] already demonstrated that NMR relaxation spectra are a powerful developmental indicator to characterize the physiological age of the leaf in Brassica napus. The similarity of the tobacco leaf NMR signal and its agreement with physiological measurements confirms the potential of NMR to provide a universal index of development whatever the plant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inversion of the relative expression levels of these two genes defines the onset of leaf senescence. More recently, it was demonstrated that cellular structural changes associated with leaf senescence can be monitored by noninvasive 1 H-NMR relaxometry (Musse et al 2013;Sorin et al 2015). In addition, the NMR signal captured chloroplast dismantling and was therefore judged to be a precise indicator of leaf senescence (Sorin et al 2015); it has been tested on two genotypes showing contrasting responses to N depletion (Sorin et al 2016).…”
Section: Following the Senescence Process In Rapeseedmentioning
confidence: 99%